Optimasi Produksi Donat di Usaha O’Om Donuts untuk Mencapai Keuntungan Maksimal dengan Program Linier Metode Grafik - Jaya, Asirman; Sukma, Silvia Antana; Utomo, Pradita Eko Prasetyo; Khaira, Ulfa (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
Small and Medium Enterprise (SME) in the culinary sector, such as O'om Donuts, explore innovation in unique donut products. Despite creating enticing variations like Baby Donuts and Donuts, O'om Donuts faces challenges in determining the optimal production to maximize profits. This research employs the linear programming graphic method at O'om Donuts' production facility in Kota Jambi to design an efficient production strategy and minimize production costs. The research methodology involves observation, interviews, and quantitative descriptive analysis. The results indicate that the optimal solution involves producing 300 Baby Donuts and 70 Big Donuts from limited resources, yielding a maximum profit of Rp315,000. The implementation of linear programming in O'om Donuts' production is expected to enhance production efficiency and accommodate product variations, creating maximum profits for MSMEs in the diverse culinary market.